Potential of Patikala Fruit (Etlingera Elatior) In Improving The Physical Quality of Spent Layer Meat - Majid, Irmawaty; Syam, Jumriah; Mutmainnah, Andi; Akbar, Muhidal (Fakultas Peternakan, Universitas Padjadjaran, 2024)
Patikala (Etlingera elatior) is a local Indonesian plant that can be used to improve meat quality because it contains secondary metabolic compounds and acid compounds which can be used to improve the meat quality of spent layer meat. This study aims to determine the potential of patikala fruit (Etlingera elatior) as a local plant in improving the physical quality of spent layer meat. This research method used a completely randomized design,with 5 treatments and 4 replications. The research design was determined based on the amount of meat used, namely soaking spent layer meat without patikala (Etlingera elatior) extract water concentration (T0=0%), the using patikala (Etlingera elatior) extract concentration (T1=25%), patikala (Etlingera elatior) extract concentration (T2=50%), patikala (Etlingera elatior) extract concentration (T3=75%), patikala (Etlingera elatior) extract concentration (T4=100%). The parameters observed were the physical quality of the meat, namely pH, cooking loss, tenderness and water-holding capacity. The results showed that soaking patikala (Etlingra elatior) extract had a very significant effect on improving the physical quality of spent layer meat based on pH values and cooking losses, but had not significant effect on the value of tenderness and water holding capacity of meat.